ANALISIS TATA KELOLA CAGAR BUDAYA DI KABUPATEN LINGGA - Febry Chahyadi Anugrah; Novi Winarti; Sayed Fauzan Riyadi (PT. Jurnal Center Indonesia Publisher, 2024)
Cultural Heritage in Lingga Regency is spread in several areas, which requires attention. The Cultural Heritage is managed by the Lingga Regency Cultural Office by involving programs, activities sub-activities and at the same time coordinating with other related parties to succeed the management of Cultural Heritage in Lingga Regency. The purpose of this study is to analyze the Governance of Cultural Heritage in Lingga Regency using the theory of governance from Widyananda (2008) with four indicators. The method used is qualitative descriptive with 10 informants and uses data collection techniques and tools in the form of observation, interviews, and documentation. The results of the study found that in the management of Cultural Heritage in Lingga Regency that the Cultural Office involved related parties, namely the Cultural Preservation Agency, cultural activists and regional and provincial apparatus organizations to succeed in management, in its management the Lingga Regency Cultural Office encountered problems regarding geographical location, lack of budget and weak human resources owned, knowing this, the Cultural Office carries out policies to overcome these problems by submitting proposals to the National Research and Development Agency for Culture, collaborating with other related agencies and by conducting routine mutual assistance to Cultural Heritage. In the process of Cultural Heritage Governance in Lingga Regency, it can be said that there is less role in technology in the media social sector. Keywords: Lingga Regency, Governance, Cultural Heritage